Impact of Motivation and Tenure on Lecturer Competence and Performance - Hamsinah, Hamsinah (Majalah Ilmiah Bijak, 2024)
This study aims to analyze the influence of motivation and tenure on lecturer competence, which impacts lecturer performance at Universitas Indonesia Maju. The research uses a quantitative approach with a survey method. The sample consists of lecturers who have NIDN at Universitas Indonesia Maju. The variables studied include motivation, tenure, competence, and lecturer performance. Data were collected through a questionnaire that was tested for validity and reliability. The results show that motivation and tenure significantly influence lecturer competence. Furthermore, lecturer competence significantly impacts lecturer performance. Data analysis indicates that achievement motivation and longer tenure tend to enhance lecturer competence in pedagogical, personality, social, and professional aspects. High competence positively contributes to the implementation of the Tridharma of Higher Education, including teaching, research, and community service. The study concludes that efforts to improve motivation and effectively manage tenure can enhance lecturer competence and performance, ultimately improving the quality of education at Universitas Indonesia Maju.